(3TQM cdjGJ GdbGfhf aj GdWH dGHf SjfGs - (3bWH GdOjf , eMeO Hf eSYhO GdTjQGRis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3JHOC HGdaf GdKGdK CeG HYO aEf CMhL Ndb Gddg GdTjQGRi NJe Gddg dg HGdMSfi jbhd (B: (3deG cGf CYXe eTGQH GdfYe hCNUH s
(3BNQgG (B:s
(3dYdg jLO eNQLkG UGdMkG dh Obb GdfXQ , hefgGLkG hGVMkG dhdGMX GdebUO GdeYJHQ s
(3JHOC HGdaf GdKGdK ef GdcJGH GdChds
(3bWYI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdWHs